Pyrolysis Kinetics Of Biomass - Mohd Mahzan, Muhammad Imran Afifi (Universiti Sains Malaysia, 2018)
The objective of this work was to evaluate the chemical kinetics of the biomass used which was sugarcane bagasse with parameters namely heating rates and chemical additives concentration. The chemical additive used for this experiment was phosphoric acid as it one of the best dehydrating agent to remove moisture content of the biomass. The pyrolysis process was carried out using a Thermal Gravimetric Analyzer (TGA-7) until a maximum temperature of 750°C. Sugarcane bagasse experienced three steps of weight loss. The decomposition of hemicellulose, cellulose and lignin are the three steps of weight loss for the biomass used. A change in the operational condition (heating rate) gives very little impact of the kinetics of the process and also the three steps weight loss. For the addition of chemical additives, it can be concluded that by impregnating the biomass with the mentioned chemical additives gives significant impact on the kinetics of the biomass.